Florida's lost galleon : the Emanuel Point Shipwreck - Smith, Roger C., 1949-; Benchley, Elizabeth D. (University Press of Florida, 2018)
This scholarly trade book tells the story of the Emanuel Point Shipwreck, recounting its discovery, subsequent archival and archaeological investigations, analysis of recovered materials, and interpretation of its role in the 1559 fleet of Tristán de Luna. This book provides a timely and comprehensive accounting of shipwreck research that is written and presented with general readers and scholars in mind.